Efeito de nanofilmes depositados a plasma na resistência de união de um cimento resinoso a uma cerâmica à base de zircônia - Figueiredo, Viviane Maria Gonçalves de [UNESP] (2014)
This study aimed to evaluated the effects of differents plasma nanofilms on the bond strength between resin cement and zirconia ceramic. 120 blocks / specimens (15.2 x 12.5 x 1.7 mm) and 18 discs (11.0 x 1.4 mm) of zirconia (Y-TZP) (VITA In-Ceram Zirconia, Vita Zahnfabrik, Germany) received differents treatments surface (n = 20 for the blocks) (n = 3 for discs): untreated zirconia (Zrpolida), silica-coated (30 μm) (Zrjat#), silica nanofilm (ZrSiO2), sandblasted by air-borne particle abrasion with aluminum oxide particles (45 μm) + silica nanofilm (Zrjat+SiO2) and fluoride nanofilm (ZrF) and sandblasted by air-borne particle abrasion with aluminum oxide particles (45 μm) + fluoride nanofilm (Zrjat+F). The nanofilms were deposited by PECVD technique of the plasma. The ceramic surfaces were characterized by morphology (SEM and AFM), chemical (XPS) and wettability (Contact angle), that was performed on discs. The silane agent was applied to each surface treatment and a cylinder of resin cement was built on the specimens. Half of the samples of each group (n = 10) were subjected to 6.000 thermalcycles. The bond strength was evaluated by shear test and fractographic analysis by stereoscopic, SEM and EDS. Statistical analysis was performed using one-way ANOVA and Tukey's test for the presence and absence non-aged (p = 0.05). Zirconia presented more hydrophilic after nanofilms deposition. Chemical bonds between Si-O were found in ZrSiO2; ZrF promotes a process of fluorination on the Y-TZP surface, promoting the conversion of zirconia in zirconium oxyfluoride. The initial values of bond strength obtained by plasma treatment did not exceed the bond values of the silica-coated. After aging, all samples of the group ZrSiO2 (TC) falied. The values of bond strength of ZrF (TC) (3.8 MPa) were lower than Zrjat# (TC) (15.4 MPa) and Zrpolida (TC) (6.3 MPa). The silica nanofilm showing detachment after shearing. Adhesive failures were predominant among the...